Quality graduates through structured co-curricular activities - Mohamad, Nor Asiah (2011)
Quality graduates is being described as employable graduates, holistic graduates, all rounded and well balanced personalities of graduates.These terms specifically reflect the expected product of the Malaysian higher learning institutions. The feedback from the stakeholders seems to support various theories suggesting that universities graduates lack in various human basic skills. It is also suggested that there is a mismatch of courses offered by the universities in comparison to the demand of workforce in the industries. Based on these premises, the Ministry of Higher Education Malaysian (MOHE) ha identified 7 thrust of soft skills and instructed the universities to employ them in teaching and learning. In International Islamic University Malaysia (IIUM), the emphasis on the relationship between knowledge and human basic skills has been the core agenda of the university. This paper analyses the university programmes towards producing well balanced graduates. The evidences so far positively support the vision and mission of the university while acknowledging the ongoing challenges ahead. The methodology is a mixed qualitative and quantitative approach. The research looks at all the policies , programmes as well as the activities designed for the students. Result of surveys conducted to measure the effectiveness of identified skills is discussed. Secondary data is utilized when relevant.